PENGARUH LATIHAN SMALL SIDED GAMES TERHADAP KETERAMPILAN PASSING PADA TIM FUTSAL SDN 163 PEKANBARU - Fauzi, Viky Rahmat; Sulastio, Agus; ,, Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The purpose of this study was to determine the effect of small sided games passing training on passing skills in the SDN 163 Pekanbaru Futsal Team. The research location is planned at the SDN 163 Pekanbaru field located on Jalan HR Soebrantas, West Sidomulyo, Tampan District, Pekanbaru City, on October 8, 2024 to November 12, 2024 at 16.00 - 18.00. Based on the analysis carried out, the t-count value between the initial test and the final test showed a figure of 3.406. Furthermore, the value obtained was compared with the t table at a significance level of 0.05 with degrees of freedom N - 1 (14) which showed a figure of 1.771, so it can be concluded that the hypothesis is accepted and there is a significant influence of the two variables. Based on the findings and data processing above, it can be concluded as follows: There is an Effect of Small Sided Games Training (X) on Passing Skills (Y) in the SDN 163 Pekanbaru Futsal Team. Based on the researcher's view on passing skills, Small Sided Games training skills can reap maximum results due to the habits carried out by each individual athlete. Keyword: Small Sided Games Drills, Passing Skills